Is candlestick continuation patterns applicable in Malaysian stock market? - Chin, Chee-Ling; Jais, Mohamad; Sulong Balia, Sophee; Tinggi, Michael (2017)
Technical analysis is deemed to be an anathema to the modern finance theory as it contradicts with the efficient market hypothesis, typically the weak form market efficiency which forbids the utilization of past prices and trading volume data to predict future market movement.However, the technical indicator of candlestick trading strategy is widely applied by traders for short term investment.This study thus investigates on the predictive power of candlestick charting which concentrates on the application of continuation patterns in Malaysian stock market from 2000 to 2014.Skewness adjusted t-test is employed to test the statistical significance of candlesticks’ profitability.After taking into account the transaction costs, sub-sample, and out-of-sample test, the findings show that only Falling Window pattern after a prevailing downtrend shows predictive power with bearish signals indicated significantly during the 5- day holding period.